SIRANERISK: Modelling dispersion of steady and unsteady pollutant releases in the urban canopy. (September 2016) - Soulhac, L.; Lamaison, G.; Cierco, F.-X.; Ben Salem, N.; Salizzoni, P.; Mejean, P.; Armand, P.; Patryl, L.
Abstract: SIRANERISK is an operational model for the simulation of the dispersion of unsteady atmospheric releases of pollutant within and above an urban area. SIRANERISK is built on the same principles as the SIRANE model, and couples a street network model for the pollutant transfers within the urban canopy with a Gaussian puff model for the transfers above it. The performance of the model are here analysed by a detailed comparisons with wind-tunnel experiments. These experiments concern the dispersion of steady and unsteady pollutant releases within and above obstacle arrays with varying geometrical configurations, representing different topologies of idealised urban districts. The overall good agreement between numerical and experimental data demonstrates the reliability of SIRANERISK as an operational tool for the assessment of risk analysis and for the management of crises due to the accidental release of harmful airborne pollutants within a built environment. Graphical abstract: Highlights: SIRANERISK is a new operational dispersion model for unsteady releases of pollutant within a built environment. The model is validated against wind tunnel experiments. SIRANERISK is a reliable tool to estimate effects of accidental releases of harmful pollutant.